From craftsmen to capitalists German artisans from the Third Reich to the Federal Republic, 1939-1953 - McKitrick, Frederick L. (Monographs in German history, 2016)
Contents -- Tables and Figures -- Acknowledgments -- Preface -- Note on the Handwerk Trades -- Abbreviations and Acronyms -- Part I - Handwerk in Crisis, 1918-1933 -- Chapter 1 - From Zünfte to Nazism: German Handwerk to 1939 -- Part II - Handwerk at War, 1939-1945 -- Chapter 2 - Handwerk in the War Economy, 1939-1941 -- Chapter 3 - The Speer Ministry, 1942-1945: The Coordination of Industry and Handwerk -- Part III - The Occupation Period, 1945-1949: The Confrontation with the American Free Market -- Chapter 4 - The First Stages of the Occupation and the Revival of Handwerk Institutions in the West -- Chapter 5 - The Legal Consolidation of Handwerk Corporatism in the British Zone -- Chapter 6 - Developments in the US Zone Leading up to the Introduction of Gewerbefreiheit -- Chapter 7 - The Role of Organization and Leadership in the Modernization of Handwerk -- Part IV - The Early Federal Republic, 1949-1953: Revolution in the German Mittelstand -- Chapter 8 - The Effects of Gewerbefreiheit on Handwerk -- Chapter 9 - The Integration of Handwerk Organizations into the Political Fabric of the Federal Republic -- Chapter 10 - Changes in the Structure and Outlook of Handwerk -- Chapter 11 - The Handwerk Act of 1953 -- Conclusion - Revolution in Handwerk? -- Bibliography -- Index